Parental experience of the neuromotor development of children with congenital heart disease: an exploratory qualitative study - Elena Mitteregger; Martina Wehrli; Manuela Theiler; Jana Logoteta; Irina Nast; Brigitte Seliner; Beatrice Latal (BMC, 2021)
Abstract Background Children with severe congenital heart disease (CHD) are a group of children at risk for neurodevelopmental impairments. Motor development is the first domain to show a delay during the first year of life and may significantly contribute to parental concerns, stress, and difficulties in early child-parent attachment. Thus, the aim of the study was to better understand the wishes and concerns of parents of children with CHD and explore their experience of their children's neuromotor development in the first year of life. Methods In this qualitative study, fourteen families were recruited. Their children were aged 1-3 years and had undergone open heart surgery within the first 6 months of life. Semi-structured interviews were audio-recorded and transcribed. The data was explored within an expert group, and a qualitative content analysis was conducted using VERBI MAXQDA software 2020. The study was conducted in accordance with the COREQ checklist. Results Parents of children with CHD reported several burdens and needs. Parental burdens concerned the child's motor development, their own physical and psychological strain, and difficulties in communication with healthcare professionals. The needs, parents reported included supporting their child's motor development, a medical coordinator, and better communication between healthcare professionals and parents. During the first phase of their children's illness, parents underwent a dynamic transitional phase and expressed the need to rely on themselves, to trust their children's abilities, and to regain self-determination in order to strengthen their self-confidence. Conclusions It is essential to involve parents of children with CHD at an early stage of decision-making. Parents are experts in their children and appreciate medical information provided by healthcare professionals. Interprofessional teamwork, partnering with parents, and continuous support are crucial to providing the best possible care for children and their families. Family-centred early motor intervention for CHD children might counteract the effect of parental overprotection and improve children's motor development and thus strengthen child-parent interaction. In future work, we aim to evaluate a family-centred early motor intervention for children with CHD developed on the basis of this qualitative study. Trial registration Not applicable.